ENFORCEMENT OF LEGAL TERMS OF HOUSEHOLDS ESTABLISHMENT ON THE ESTABLISHMENT OF MOSQUE IN SUKAJADI DISTRICT, BANDUNG - Aulia Hestyara (Jurnal Ilmu Hukum, 2020)
Indonesia, through the 1945 Constitution of the Republic of Indonesia, provides a constitutional guarantee for the principles of freedom and equality. This is reflected directly in the 1945 Constitution Chapter XA, which regulates Human Rights. This includes religious freedom, and thus as a consequence, the State needs to regulate the procedures for carrying out the construction of places of worship. In Indonesia, the procedures for implementing the construction of houses of worship are regulated specifically in the Joint Regulation of the Minister of Religion and the Minister of Home Affairs number 8 & 9 of 2006 concerning Guidelines for Implementing the Duties of Regional Heads / Deputy Regional Heads in Maintaining Religious Harmony, Empowering Forum for Religious Harmony, and Establishing Houses Worship. In practice, however, the implementation of this Regulation still has several obstacles and the construction of certain houses of worship, especially for houses of worship for adherents of minority religions. It is well known that Indonesia is a country with a majority Muslim population. For Muslims, the construction of houses of worship, namely mosques, tends to be easier. However, behind this convenience, it is necessary to examine further whether all the requirements as formulated in the PBM for the Establishment of Houses of Worship have fulfilled in terms of mosque construction.